Distribution of temperament/mizāj among patients with knee osteoarthritis: a cross-sectional study - Farooq, Fouzia; Hanief, Mir Idrees; Javed, Ghazala; Ahmed, N. Zaheer (International Journal Of Community Medicine And Public Health, 2026)
Background: Knee osteoarthritis (KOA) is a common degenerative joint disorder with multifactorial etiology. While established risk factors such as age, obesity, and mechanical stress are well known, constitutional factors like temperament (Mizāj) described in Unani medicine remain underexplored. Hence the present study was conducted to describe the distribution of Mizāj among patients with KOA. Methods: A hospital-based cross-sectional study was conducted at the Regional Research Institute of Unani Medicine (RRIUM), Srinagar, from April to October 2021. A total of 60 patients aged 40-70 years with clinically and radiologically confirmed KOA (Kellgren-Lawrence grade I and II) were included. Mizāj was assessed using a structured proforma based on classical Unani parameters. Data were analyzed using SPSS version 20.0. Descriptive statistics (frequencies and percentages) were calculated, and the Chi-square test was applied, with p<0.05 considered statistically significant. Results: Balghamī Mizāj was observed in 52 (86.67%) patients, followed by Damawī Mizāj in 5 (8.33%) and Ṣafrāwī Mizāj in 3 (5%). No cases of Sawdāwī Mizāj were found. The difference in the distribution of temperament was not statistically significant (χ2=2.21, df=2, p=0.509). Conclusions: KOA was found to be more prevalent among patients with Balghamī Mizāj and may therefore be considered a predominantly phlegmatic disorder (Marad-i-Balghamī) or a manifestation of phlegmatic distemperament (Sūʾ-e-Mizāj Balghamī). However, in view of the lack of statistically significant association and the cross-sectional nature of the study, these findings should be interpreted with caution, and further analytical studies are warranted to substantiate this observation.